2009
DOI: 10.1007/s10735-009-9250-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 expression in astrocytes and microglia in human oligodendroglioma and astrocytoma

Abstract: Cyclooxygenases (cox) are potent mediators of inflammation and two cox-isoenzymes, cox-1, cox-2, are described to date. Cox-2 is cytokine-inducible in inflammatory cells and enhanced cox-2 expression has been attributed a key role in the development of edema and immunomodulation in pathologically altered brain tissues. In normal cerebral cortex cox-2 is present only in neurons, but not in the glial or vascular endothelial cells. The function of microglia in glioma biology is unclear. Microglia have both neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
0
21
1
Order By: Relevance
“…First, EGFR signaling is known to be involved in OPC proliferation and tumorigenesis [43,44]. Second, the accumulation of Cox2-expressing astrocytes is more often observed in high-grade oligodendroglioma than in GBM [45,46]. Third, hGIC1 and Hs683 strongly expressed egfrvIII, which was shown by Mellinghoff et al to cause ''pathway addiction'' of the tumor cells [47].…”
Section: Discussionmentioning
confidence: 98%
“…First, EGFR signaling is known to be involved in OPC proliferation and tumorigenesis [43,44]. Second, the accumulation of Cox2-expressing astrocytes is more often observed in high-grade oligodendroglioma than in GBM [45,46]. Third, hGIC1 and Hs683 strongly expressed egfrvIII, which was shown by Mellinghoff et al to cause ''pathway addiction'' of the tumor cells [47].…”
Section: Discussionmentioning
confidence: 98%
“…Microglial cells infiltrating brain tumors are characterized by high expression levels of cyclooxygenase-2 (COX-2) which generates prostaglandin E2 (PGE2). COX-2 is also expressed by glioma cells [18,19]. COX-2-derived PGE2, in turn, may promote the growth of experimental gliomas and contribute to edema development [20,21].…”
Section: Pathogenesismentioning
confidence: 99%
“…As the development of selective COX-2 inhibitors, their adverse effects and computer-aided drug design approaches to design effective anti-inflammatory agents with reduced side effects have been recently reviewed [71][72][73][74][75], this article focuses on the neuroinflammation aspect of COX-2 inhibitors. COX-2 is the key enzyme in the formation of prostaglandins and is expressed in activated microglial cells astrocytes [76][77][78], which appear to be an important source of prostaglandins during inflammatory conditions. COX-1 is constitutively expressed in many cell types [79].…”
Section: Cox-2 Inhibitorsmentioning
confidence: 99%
“…It was also reported that inhibition of pro-inflammatory leukotriene production could significantly enhance the inhibitory effects of NSAIDs on the neurotoxicity of microglial cells. The authors suggested using 5-LOX inhibitors in combination with NSAIDs for their synergistic beneficial effects in AD and possibly in normal aging [77]. Meanwhile, the 5-LOX inhibitor, nordihydroguaiaretic acid, inhibited TNF-a production by microglia in a mouse model of ALS [109].…”
Section: -Lox Inhibitorsmentioning
confidence: 99%